Pengaruh Flexible Working Arrangement dan Job Crafting dengan Innovative Work Behavior Aparatur Sipil Negara pada Dinas Ketahanan Pangan Kabupaten Mamuju - Ishak, Atika; Ramli S, Ramli S; Aqil, Muhammad; Nurfaidah, Nurfaidah (Pascasarjana Universitas Muhammadiyah Mamuju, 2026)
This study aims to analyze the effect of Flexible Working Arrangement and Job Crafting on the Innovative Work Behavior of civil servants at the Food Security Agency of Mamuju Regency. The research employed a quantitative approach with a survey design. The research object comprised civil servants working in the agency, with the population consisting of all active employees. The sample was determined using proportional random sampling. Data were collected through structured questionnaires and analyzed using multiple linear regression with statistical software. The results indicate that Flexible Working Arrangement and Job Crafting simultaneously have a significant effect on Innovative Work Behavior. This is evidenced by an F-value of 6.635 exceeding the F- table value of 3.29 and a significance level of 0.000 (< 0.05), leading to the acceptance of the proposed hypothesis. These findings suggest that the integration of flexible work policies and individual job crafting initiatives plays a crucial role in enhancing innovative behavior among civil servants